"Fast Track" Development and Approval Process for Heart Failure Therapeutics. Issue 2 (21st June 2017) - Papadimitriou, L; Butler, J
Abstract : Heart failure (HF) is a global epidemic, with a high mortality and morbidity burden. In such diseases, earlier access to lifesaving therapeutic regimens is imperative, and could be accomplished by improving the drug development and approval process, without jeopardizing patient safety. The US Food and Drug Administration (FDA) has already established mechanisms facilitating the latter, but further guidance to enhance and expedite the process holds promise to further improve patient outcomes.